Use of aqueous polyol monomer for superior dye separation performance and high chlorine resistance of thin-film composite polyester nanofiltration membranes. (August 2022) - Ang, Micah Belle Marie Yap; Huang, Guan-Wei; Chu, Min-Yi; Millare, Jeremiah C.; Huang, Shu-Hsien; Lee, Kueir-Rarn
Abstract: Search for efficient wastewater treatment process is still upsurging because of water scarcity brought about by continuous industrialization. This includes efforts to discover the best materials to use for possible solutions to this global problem. In this work, application of three polyols as aqueous monomers were explored as material for fabricating nanofiltration membranes for dye desalination. These polyols are D-sorbiltol (DST), pentaerythritol (PET) and erythritol (ERT). Separately, they use to react with trimesoyl chloride (TMC) on top of polyethersulfone (PES) support through interfacial polymerization. ATR-FTIR and XPS analysis confirmed the successful formation of the polyester layer. Different monomers provide different surface hydrophilicity and surface charged. These properties were mostly depending on the number of reactive sites and the chemical structure of the aqueous monomer. DST consists of 6 hydroxyl groups and a linear structure, when reacts with TMC, it produces a dense selective layer with low permeation flux. ERT with only 4 hydroxyl groups and a linear structure, produced looser polyester layer. Compared with ERT, PET has a nonlinear structure with 4 hydroxyl groups, produced denser structure, because its structure has a less steric hindrance. Furthermore, TFCERT showed a superior chlorine resistance up to 24, 000 ppm∙h. Therefore, the suitable monomer for dye desalination was ERT, where TFCERT delivered the highest water flux, high dye/salt selectivity and excellent chlorine resistance. Graphical abstract: Unlabelled Image Highlights: Polyols were used to prepare thin-film polyester membranes. Suitable chemical structure of polyols was determined. Thin-film polyester membrane had high dye separation performance. Thin-film polyester membrane had chlorine resistance.